HPV among men - what knowledge we have in this field - Jakub Fiegler-Rudol; Katarzyna Kryszczyszyn-Musialik; Karolina Lau (Śląski Uniwersytet Medyczny w Katowicach, 2024)
The human papillomavirus (HPV) is a common sexually transmitted DNA virus. The resulting infection may be asymptomatic or manifest itself through benign symptoms such as warts, affecting the genitals and skin. It is a common etiological factor associated with various cancers, most notably cervical cancer. The prevalence of genital HPV in healthy men is high and can be higher than in women in certain populations. The virus is transmitted sexually. Contraceptive methods do not protect against transmission as it can be transmitted through the skin of the scrotum. Rates vary drastically based on factors such as the country of residence, socioeconomic status, ethnicity as well as the screening methods used. Population factors affect HPV vaccine acceptance. The awareness about HPV has improved over the past two decades, with women historically being more informed. However, awareness is still inadequate, especially among certain demographic groups. Despite men currently showing similar awareness levels to women, a significant percentage have not been vaccinated. Not only are men an important vector for infection, but HPV is correlated with several cancerous changes observed among men. Attitudes towards HPV vaccination differ, with some influenced by vaccine hesitancy, which itself is correlated with knowledge. These individuals face higher risks due to lower vaccination rates for HPV.